"Systems medicine" in the view of von Bertalanffy's "organismic biology" and systems theory. (14th May 2019) - Tretter, Felix
Abstract: Currently, medicine is transforming towards molecular systems medicine (MSM), based on molecular systems biology (MSB). These approaches should be related to Ludwig von Bertalanffy's vision of "organismic" systems biology/medicine (OSB/OSM) and of general system theory (GST), which he created already in the 1930s. In this paper, on the basis of current diversity of knowledge in medicine, major differences between MSB/MSM and OSB/OSM are highlighted: MSB is based on biochemical high‐throughput technologies, sophisticated mathematical data analytical tools, and supercomputers for computation, whereas OSB is based on developmental biology and is concept and theory oriented. Metatheoretical considerations show that holistic but still reductive MSM cannot bridge the categorical molecule–cell difference, the mind–body difference, and the environment–organism gap by a consistent molecular and mechanistic theory of the organism. In contrast, the options of theoretical interlevel modelling with the help of simply structured but complexly functioning organ models are discussed here. As example, the neurochemical mobile of the brain is discussed. Consequently, a reconsideration of GST in medicine, targeting OSM, seems to be fruitful by linking MSM with a core concept of a systems pathology and with psychosocial and clinical medicine.